Faktor-Faktor Yang Mempengaruhi Kinerja Manajer Perhotelan Pada Masa Pandemi Covid-19 Di Parepare Sulawesi Selatan - Sudirman, Irmayanti; Frihatni, Andi Ayu; Mandacan, Frengky; Sundari, Sri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This research aims to analyze promotion costs and quality of service to the performance of managers during the COVID-19 pandemic. This type of research is quantitative conducted at Parepare, South Sulawesi. The sample of the research was all hotels in Parepare of 25 hotels. The data analysis used is a multiple regression. The result of this research discloses that promotional costs and service quality affect the hotel manager performance in Parepare. Another result discloses that promotional costs have more effect on hotel revenue compared to the quality of hotel services quality. This is because promotion costs are the costs incurred for the activities carried out by the hotel to increase room service and to create other service products. The results of this study are expected to contribute to the hotel sector in increasing revenues during the pandemic.